Milton and the parables of Jesus: self-representation and the Bible in John Milton's writings - Urban, David V. (Medieval & Renaissance literary studies, 2018)
"Examines Milton's identification with characters in Jesus's parables. Connects Milton's engagement with the parables to his self-representation throughout his poetry and prose"--Provided by publisher